Clinical management of chronic abscess in an Asian elephant (Elephas maximus) - Senthilkumar, Kadirvelu; Senthilkumar, Alagumalai; Jayathangaraj, Madurai Ganesan (Journal of Advanced Veterinary and Animal Research, 2014)
Regional perfusion with Triple sulpha was used to treat a severe abscess in a 7-year old female Asian elephant (Elephas maximus) housed at a temple in Tamil Nadu, India. The cow elephant was presented with an acute swelling at left shoulder that persisted despite 4 days of anti-inflammatory therapy. There was a 3-cm-deep, 5-cm-diameter abscess pocket that was subsequently debrided. Regional perfusion was performed by using 7% Tincture iodine for 15 days, and Triple sulpha in the wound pocket. Besides, the elephant received Enrofloxacin (dosed at 10 mg/kg b.wt.) and Meloxicam (dosed at 0.2 mg/kg b.wt.) intramuscularly. Within 2 days of administering the first perfusion, the swelling reduced dramatically. After 7 days of successive treatment, the elephant showed marked improvement. The affected skin area became normal after 60 days post-treatment. DOI: http://dx.doi.org/10.5455/javar.2014.a9 J. Adv. Vet. Anim. Res., 1(2): 73-74, June 2014